Clinical Characteristics and Outcomes of 821 Older Patients With SARS-Cov-2 Infection Admitted to Acute Care Geriatric Wards: A Multicenter Retrospective Cohort Study. (26th August 2020) - Zerah, Lorène; Baudouin, Édouard; Pépin, Marion; Mary, Morgane; Krypciak, Sébastien; Bianco, Céline; Roux, Swasti; Gross, Ariane; Toméo, Charlotte; Lemarié, Nadège; Dureau, Antoine; Bastiani, Sophie; et al.
Abstract: Background: There is limited information describing the characteristics and outcomes of hospitalized older patients with confirmed coronavirus disease 2019 (COVID-19). Method: We conducted a multicentric retrospective cohort study in 13 acute COVID-19 geriatric wards, from March 13 to April 15, 2020, in Paris area. All consecutive patients aged 70 years and older, with confirmed COVID-19, were enrolled. Results: Of the 821 patients included in the study, the mean ( SD ) age was 86 (7) years; 58% were female; 85% had ≥2 comorbidities; 29% lived in an institution; and the median [interquartile range] Activities of Daily Living scale (ADL) score was 4 [2–6]. The most common symptoms at COVID-19 onset were asthenia (63%), fever (55%), dyspnea (45%), dry cough (45%), and delirium (25%). The in-hospital mortality was 31% (95% confidence interval [CI] 27–33). On multivariate analysis, at COVID-19 onset, the probability of in-hospital mortality was increased with male gender (odds ratio [OR] 1.85; 95% CI 1.30–2.63), ADL score <4 (OR 1.84; 95% CI 1.25–2.70), asthenia (OR 1.59; 95% CI 1.08–2.32), quick Sequential Organ Failure Assessment score ≥2 (OR 2.63; 95% CI 1.64–4.22), and specific COVID-19 anomalies on chest computerized tomography (OR 2.60; 95% CI 1.07–6.46). Conclusions: This study provides new information about older patients with COVID-19 who are hospitalized. A quick bedside evaluation at admission of sex, functional status, systolic arterial pressure, consciousness, respiratory rate, and asthenia can identify older patients at risk of unfavorable outcomes.